74.4: Invited Paper: What Lies Beyond Multitouch?. Issue 1 (June 2015) - Harrison, Chris
Abstract : Seven years ago, multi‐touch devices went mainstream, and changed the industry and our lives. In that time, mobile devices have gotten much more capable, yet the core user experience has evolved little. Contemporary touch gestures rely on poking screens with different numbers of fingers: one‐finger tap, two‐finger pinch, three‐finger swipe and so on. We often label these as "natural" interactions, yet the only place I perform these "gestures" is on my touchscreen device. We are also too quick to blame the "fat finger" problem for much of our touch interface woes — if a zipper or pen were too small to use, we would simply call that "bad design". Fortunately, our fingers and hands are amazing, and with good technology and design, we can elevate touch interaction to new heights. I believe the era of multi‐touch is coming to a close, and that we are on the eve of an exciting new age of "rich‐touch" devices and experiences.